The operation and capacity fade modelling of the lithium-ion cell for electric vehicles - Burzyński Damian; Kasprzyk Leszek (E3S Web of Conferences, 2019)
The paper deals with the issues related to the operation and capacity fade modelling of lithium-ion cells. It includes the presentation of the electrochemical model of the cell in which the phenomenon of diffusion and transfer of charge on electrodes and in electrolyte was discussed. The circuit model of the cell designed for analysis of its behaviour in the conditions of the dynamically variable load was presented. The key aging processes which occur during the operation of the cells were characterised, and their impact on the wear of the cell was discussed. The model of the capacity fade of the lithium-nickel-manganese-cobalt cell was developed. The model parameters depends on the ambient temperature, the value of load current and the value of the average charge current. The results of the model were verified with the laboratory measurement.